Surds and Indices Aptitude Test Paper 311) If 2^{x}=3^{y}=6^{z}, then is equal to
Answer: A Explanation: Given: 2^{x}=3^{y}=6^{z} Equating the powers of above equation because the base is same 12)
Answer: C Explanation: Given: Then p^{3}3p Putting the value of 'p' in above equation By applying (a+b)^{3} = a^{3} + b^{3} + 3ab(a+b) 13)
Answer: C Explanation: Given: Then, a = k^{m}, b = k^{n}, c = k^{p} abc = 1 (given) k^{m}. k^{n}. k^{p} = k^{0} k^{m+n+P} = k^{0} m+n+P = 1 Since the base are same So, m+n+P = 0 14)
Answer: D Explanation: By equating the power 5 + 8 = 2x +3 15) If 2^{x1}+2^{x+1}=320,then x is equal to
Answer: D Explanation: By equating the powers x6 = 1 Surds and Indices Test Paper 1 Surds and Indices Test Paper 2 Surds and Indices Test Paper 4 Surds and Indices Concepts
Next TopicSurds and Indices Aptitude Test Paper 4
